A Cross-Version Approach to Audio Representation Learning for Orchestral Music - Krause, Michael; Weiß, Christof; Müller, Meinard (Proceedings of the International Society for Music Information Retrieval Conference (ISMIR), 2023)
Deep learning systems have become popular for tackling a variety of music information retrieval tasks. However, these systems often require large amounts of labeled data for supervised training, which can be very costly to obtain. To alleviate this problem, recent papers on learning music audio representations employ alternative training strategies that utilize unannotated data. In this paper, we introduce a novel cross-version approach to audio representation learning that can be used with music datasets containing several versions (performances) of a musical work. Our method exploits the correspondences that exist between two versions of the same musical section. We evaluate our proposed cross-version approach qualitatively and quantitatively on complex orchestral music recordings and show that it can better capture aspects of instrumentation compared to techniques that do not use cross-version information.<br